Development of a polyclonal antisera-based coagglutination assay for the detection of local strains of Vibrio cholerae 01 - Gonzales, Ma. Carline G. (2003)
Cholera continues to be a public health concern in the Philippines. Its rapid diagnosis is critical in the prevention of potential local outbreaks of cholera. Immuno-diagnostic assays for cholera have come to age and have becme readily available. These assays are capable of providing quick, accurate results needed in controlling this infection through prompt treatment of cholera cases. One such assay is the coagglutination assay, which has been reported to be accurate and sensitive in detecting cholera vibrios in stool samples. In this study, a polychlonal-based coagglutination assay was developed for detecting local strains for Vibrio cholerae 01, by using a vaccine prepared from polysccharide extracts of a local isolate of Ogawa strain and reference strain Inaba D230. Polyclonal antiserum was raised in rabbits immunized using the polysaccharide-bovine serum albumin conjugate vaccine. The rabbits achieved the peak immune response 33 days after first immunization. The highest titer for anti-Inaba antibodies was 4096 and 256 for anti-Ogawa antibodies. Equal amounts of pooled antiserum raised against each strain were mixed to prepare the In-house Vibrio cholerae 01 polyclonal antiserum. This In-house polyclonal antiserum had a higher sensitivity in detecting 9.38 x 107 cells per ml for either strain, than a commercially available Bacto? poly antiserum which had a sensitivity of detecting 1.88 x 108 cells per ml. The In-house polyclonal antiserum and Bacto poly antiserum (positive control) were used to sensitize stabilized staphylococci (ATCC strain 25923) cells to prepare the coagglutination test (COAT) reagent. It was determined that 2% was optimal concentration of sensitized staphylococcal cells that produced the best agglutination reaction. Varying amounts of In-house polyclonal antiserum was used to sensitize 1.0 ml. of staphylococcal cells (10% suspension). It was found that 4.0 ml. of polyclonal antiserum gave the optimal agglutination reaction based on the strength/degree and the shortest time for agglutination to occur. This In-house COAT reagent, at 2% concentration, was capable of detecting 2.907 x 106 Inaba cells and 5.752 x 106 Ogawa cells. However based on a previous study which used only 0.2 ml of antiserum to prepare COAT reagent, an In-house CAOT reagent using only 0.2 ml of the In-house and Bacto (for positive control) polyclonal antiserum was als prepared. It was observed that although the In-house COAT reagnet (at 2%) prepared using 4.0 ml of In-house antiserum had a higher sensitivity than COAT reagents prepared using only 0.2 ml of the In-house and Bacto antiserum, the 0.2 ml of antiserum was already sufficient in increasing the sensitivity in detecting V. cholerae 01 than when uwing either polyclonal antiserum alone. At 3.3%, 2.5% and 2% concentration, the In-house COAT reagent prepared with 0.2 ml antiserum had a higher sensitivity than the In-house polyclonal antiserum and the Bacto poly antiserum used alone, a well as the Bacto COAT reagent. The detection limit at 2% of this In-house COAT reagent was >/- 5.86 x 106 Inaba cells per ml and >/- 2.34 x 107 Ogawa cells per ml. However, it was noted that the In-house COAT reagents took longer to agglutinate Vibrio cholerae 01 as compared with the Bacto COAT reagent. In-house COAT reagent did not cross-react with Aeromonas sp., Escherichia coli, Salmonella typhi, Shigella flexneri, Shigella dysenteriae and Vibrio parahemolyticus. Further studies to determine the sensitivity of the COAT using stool samples from suspected cholera patients need to be conducted to better assess its local applicability.